A highly efficient electrocatalyst based on double perovskite cobaltites with immense intrinsic catalytic activity for water oxidation. Issue 7 (20th December 2019) - Andersen, Håkon; Xu, Kaiqi; Malyshkin, Dmitry; Strandbakke, Ragnar; Chatzitakis, Athanasios
Abstract : OER electrocatalysts based on double perovskite cobaltites (Ln = Gd or Pr) with intrinsic catalytic activities exceeding that of IrO2 . Abstract : High temperature electrocatalysts based on double perovskite cobaltites that are typically employed in proton ceramic fuel cells and electrolyzers are exploited here for room temperature water oxidation. The double perovskites are assessed by the R ct C dl product and we show that their intrinsic catalytic activities exceed that of IrO2 .